Research on the Data Elements Enabling New Quality Productivity Mechanisms, Challenges, and Pathways - Xue Yuheng (SHS Web of Conferences, 2025)
Data component, as a novel production element, is the primary catalyst for advancing new quality productivity. This paper finds that there are three mechanisms for data factors to empower new quality productivity. First, data factors give birth to new quality production materials such as artificial intelligence model; Second, data factors have broken through the objective limitations of traditional production factors and created a large number of new industries, new forms of business and new models. Third, under the interaction between data elements and employment practices, a new quality labor force adapted to the development of the digital economy era has been cultivated. In view of the triple contradictions between openness and security, efficiency and fairness, and property rights and income in the process of empowerment, this study puts forward the triple ideas of establishing a standardized and transparent data governance system, constructing a “technology-ethics” dynamic adjustment mechanism, and innovating value distribution mode, so as to further promote the release of data element value and promote the development of new quality productivity. At the same time, it provides a reference for relevant scholars to understand the relationship between data elements and new quality productivity.